Beyond Teacher Competence: Uncovering the Key Determinants of Student Learning and Achievement of Islamic Religious Education Subjects - Muhammad Akmansyah; Indah Aprilia Putri; Nurnazli Nurnazli; Amin Mujahid (Nurul Jadid University, 2026)
This study examines the extent to which teachers' professional competence influences students' learning activities and cognitive learning outcomes in Islamic Religious Education (PAI). The Research was motivated by the widespread assumption in educational policy that improving teacher competence is a primary pathway to enhancing learning quality. This assumption has received mixed empirical support. Employing a descriptive quantitative design, data were collected from 157 eleventh-grade students at a public senior high school in Indonesia using questionnaires, academic documentation, and classroom observations. Teachers' professional competence and students' learning activities were measured through Likert-scale instruments, while cognitive learning outcomes were obtained from school records. Data were analyzed using descriptive statistics, hypothesis testing, and simple and multiple linear regression. The findings reveal that teachers' professional competence has no statistically significant effect on students' learning activities or cognitive learning outcomes. Regression models demonstrate very low explanatory power, indicating that professional competence accounts for only a minimal proportion of variance in both dependent variables. Visual analysis using scatter plots further confirms the absence of meaningful linear relationships. These results suggest that student engagement and achievement in PAI are shaped by broader factors beyond teachers' professional competence alone. The study highlights the importance of adopting a more holistic perspective on educational effectiveness that integrates student agency, classroom interaction, and contextual learning environments.